2014
DOI: 10.1108/jeim-06-2013-0031
|View full text |Cite
|
Sign up to set email alerts
|

The effects of transformational leadership and ERP system self-efficacy on ERP system usage

Abstract: Purpose – During the past decade, there has been vast investment in Enterprise Resource Planning (ERP) system packages, in addition to a significant increase in the importance of acceptance by users of the ERP system regarding the success or failure of ERP implementation. The purpose of this paper is to identify the external factors which influence ERP system acceptance. The work is motivated by the realization that transformational leadership (TL) and ERP system self-efficacy are critical exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
38
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 69 publications
5
38
1
Order By: Relevance
“…In portraying the following traits, transformational leaders can inspire, encourage, empower, and influence project team members to work toward the common objective of a successful implementation. When leaders encourage creativity through transformational leadership, users are more likely to experiment with the system features, enabling them to learn the system more quickly (Elkhani et al, 2014). Additionally, transformational leadership can create a higher level of psychological empowerment (PE), commitment to the project, and trust (Mittal, 2016).…”
Section:  Managerial Theories In Erp Implementationsmentioning
confidence: 99%
See 3 more Smart Citations
“…In portraying the following traits, transformational leaders can inspire, encourage, empower, and influence project team members to work toward the common objective of a successful implementation. When leaders encourage creativity through transformational leadership, users are more likely to experiment with the system features, enabling them to learn the system more quickly (Elkhani et al, 2014). Additionally, transformational leadership can create a higher level of psychological empowerment (PE), commitment to the project, and trust (Mittal, 2016).…”
Section:  Managerial Theories In Erp Implementationsmentioning
confidence: 99%
“…Another leadership theory that is compared to transformational leadership is servant leadership. In comparing the two theories, it has been found that transformational leaders focus on organizational objectives while servant leaders focus on people as followers (Elkhani et al, 2014). Introduced by Greenleaf (1970Greenleaf ( , 1977, servant leadership includes ethics, virtues, and morality and has been noted as a model that may assist a leader in dealing with issues that arise within an organization.…”
Section: Servant Leadership Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…In literature, factors influencing the success of enterprise ERP implementation have been quite widely discussed, as well as the need to improve approaches and implementation methods. [1][2][3][4] Some of the works are also devoted to the specifics of multi-plant enterprise management and the functioning of their ERP systems [5][6][7]. In the article using a case study of the implementation of one of the Polish ERP systems of Macrologic in several multi-plant enterprises, it demonstrates how it improved the functioning and organization of processes in these companies.…”
Section: Introductionmentioning
confidence: 99%